2019
DOI: 10.3390/jcm8112008
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electromagnetic Field Therapy Improves Osseous Consolidation after High Tibial Osteotomy in Elderly Patients—A Randomized, Placebo-Controlled, Double-Blind Trial

Abstract: Extremely low-frequency pulsed electromagnetic field (ELF-PEMF) therapy is proposed to support bone healing after injuries and surgical procedures, being of special interest for elderly patients. This study aimed at investigating the effect of a specific ELF-PEMF, recently identified to support osteoblast function in vitro, on bone healing after high tibial osteotomy (HTO). Patients who underwent HTO were randomized to ELF-PEMF or placebo treatment, both applied by optically identical external devices 7 min pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 43 publications
3
17
0
3
Order By: Relevance
“…The effectiveness of the ELF-PEMF was confirmed in further studies, both in vitro and in vivo [25,29]. Comparing the effect on bone formation in this in vivo study [29] with other studies that used 4-to 200-times longer daily exposures revealed that increasing the exposure duration may enhance the observed effects [9]. Thus, in the present study, exposure duration was varied at first.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The effectiveness of the ELF-PEMF was confirmed in further studies, both in vitro and in vivo [25,29]. Comparing the effect on bone formation in this in vivo study [29] with other studies that used 4-to 200-times longer daily exposures revealed that increasing the exposure duration may enhance the observed effects [9]. Thus, in the present study, exposure duration was varied at first.…”
Section: Discussionsupporting
confidence: 73%
“…A screening approach identified ELF-PEMFs in this frequency range to best support the viability and differentiation of osteoprogenitor cells [12]. The effectiveness of the ELF-PEMF was confirmed in further studies, both in vitro and in vivo [25,29]. Comparing the effect on bone formation in this in vivo study [29] with other studies that used 4-to 200-times longer daily exposures revealed that increasing the exposure duration may enhance the observed effects [9].…”
Section: Discussionsupporting
confidence: 51%
“…For example, the 16 Hz ELF-PEMF induced osteoblast function in patients undergoing high tibia osteotomies. However, no effect on osteoclast inflammatory markers was observed [ 36 ]. By changing the frequency “window”, other cells might be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth study used an ELF-PEMF with a frequency of 15 Hz for 4 h per day for more than 1 year during limb lengthening [118]. The fifth study used an ELF-PEMF with a frequency of 16 Hz for only 7 min per day for 30 days following high tibial osteotomy [120]. In three studies, commercial ELF-PEMF devices were used, namely EBI stimulator (Electro-Biology Inc, Fairfield, NJ, USA) [118], BIOSTIM®(IGEA S.p.A., Carpi, Italy) [119], and Somagen®(Sachtleben GmbH, Hamburg, Germany) [120].…”
Section: Elf-pemf Treatment To Support Healing Of Osteotomiesmentioning
confidence: 99%